1996
DOI: 10.1002/j.1537-2197.1996.tb12803.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytology of 2N pollen formation and pollen morphology in diploid lotus tenuis (fabaceae)

Abstract: Two genotypes of Lotus tenuis Waldst & Kit. ex Willd. PI 204882, a diploid (2n = 2x = 12), were identified as producing 2n pollen (maximum = 6%). The objectives of this research were: (1) to determine the mechanism(s) of 2n pollen formation in the L. tenuis genotypes and (2) to morphologically describe n and 2n pollen using light and scanning electron microscopy. Meiotic studies revealed that 2n pollen resulted from tripolar spindles during anaphase II of microsporogenesis. The 2n pollen germinated well, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Higher PTGR of evolved polyploids relative to neo-polyploids may thus arise as a by-product of solving physiological problems, as opposed to higher PTGR per se being targeted by selection. Consistent with this idea, morphological abnormalities have been reported in pollen tubes of several neo-polyploids (24)(25)(26). Modeling studies show that coordination of cell size, turgor, and cell wall properties is essential for maintaining steady polar growth of pollen tubes (27), so cellular defects could in principle underlie both low PTGR and morphological defects.…”
Section: Resultssupporting
confidence: 61%
“…Higher PTGR of evolved polyploids relative to neo-polyploids may thus arise as a by-product of solving physiological problems, as opposed to higher PTGR per se being targeted by selection. Consistent with this idea, morphological abnormalities have been reported in pollen tubes of several neo-polyploids (24)(25)(26). Modeling studies show that coordination of cell size, turgor, and cell wall properties is essential for maintaining steady polar growth of pollen tubes (27), so cellular defects could in principle underlie both low PTGR and morphological defects.…”
Section: Resultssupporting
confidence: 61%
“…Other MII spindle defects leading to meiotic nonreduction are tripolar (tps) and fused (fs) spindles (Rim & Beuselinck, ). In tps, unilateral defects in MII spindle orientation lead to a rejoining of chromatids at one pole and normal separation at the other pole, producing triads with one diploid and two haploid spores.…”
Section: Cytological Processes Leading To Meiotic Restitutionmentioning
confidence: 99%
“…As these processes are generally observed together with ps, it is suggested that they are caused by a similar cytological defect and that their level of appearance only depends on the severity of the underlying defect (Veilleux & Lauer, ). Male‐specific meiotic restitution through ps, tps and fs has been documented in a large set of plant species (Souter et al ., ; Parrott & Smith, ; Teoh, ; Conicella et al ., ; Rim & Beuselinck, ; Genualdo et al ., ; Lopez‐Lavalle & Orjeda, ; Crespel et al ., ; Zhang & Kang, ), and is therefore considered to be the predominant route for 2n gamete formation in plants. However, despite the high prevalence, the exact cytological anomaly underlying this type of meiotic restitution is still unknown.…”
Section: Cytological Processes Leading To Meiotic Restitutionmentioning
confidence: 99%
“…Cell fusion (SPIES 1993), presence of B chromosomes (SHAH 1963(SHAH , 1964 and different abnormalities occurring during microsporogenesis (RAMANNA 1979;BRETAGNOLLE and THOMPSON 1995;RIM and BEUSELINCK 1996) give rise to non reduced gametes and, hence, to 2n pollen; this pollen is usually larger in size than n pollen and size differences can even be detected at the optic microscope (MACEIRA et al 1992).…”
Section: Cell Fusion and Pollen Size Differencesmentioning
confidence: 99%